Perspectives of preschool children in England with speech and language needs in the development of evidence‐based activities. (5th February 2020) - Coad, Jane; Harding, Sam; Hambly, Helen; Parker, Naomi; Morgan, Lydia; Marshall, Julie; Roulstone, Susan
Abstract: Background: The existing evidence is limited in terms of perspectives of preschool children with speech and language needs and their views on activities used to support their needs. This paper discusses a stream of work from the interdisciplinary research programme known as "Child Talk, " based in England, UK. The overall purpose of this work stream was to gain the perspectives of preschool children aged 2 to 5 years and 11 months, with speech and language needs, to use in the development of an evidence‐based framework of activities. Methods: Twenty‐four preschool children with a variety of needs from diverse backgrounds took part. An observational methodology was used to capture children's experiences. Children were filmed during a series of sessions, with innovative head‐mounted cameras worn by the children and supported by researcher field notes. Framework analysis was used to analyse the data based on the body movement, vocalization, and visual attention of the children during these sessions. Results and Conclusions: Results included that children expressed enjoyment and engagement in the activities. The children expressed themselves and demonstrated their focus "multimodally" through combinations of body language, vocalization, and visual attention. These modalities were present across all contexts and children. It highlights the importance of encouraging participation in preschool children and consequently this innovative piece of work has national and international importance.